International Conference on Innovative Computing and Communications Proceedings of ICICC 2018, Volume 1 - Bhattacharyya, Siddhartha; Hassanien, Aboul Ella; Gupta, Deepak; Khanna, Ashish; Pan, Indrajit (Lecture Notes in Networks and Systems, 2019)
The book includes high-quality research papers presented at the International Conference on Innovative Computing and Communication (ICICC 2018), which was held at the Guru Nanak Institute of Management (GNIM), Delhi, India on 5-6 May 2018. Introducing the innovative works of scientists, professors, research scholars, students and industrial experts in the field of computing and communication, the book promotes the transformation of fundamental research into institutional and industrialized research and the conversion of applied exploration into real-time applications.